Interaction Between Gelatin and Cationic Gemini Surfactant with Long Unsaturated Tail - Chen, Xiaoming; Ren, Lin (Asian Journal of Chemistry, 2013)
The interaction of cationic gemini surfactant 1,2-ethane-bis-[N,N,N-dimethyl-(Z-13- docosenyl)quaternary ammonium bromide] (hereafter noted 22-2-22) with gelatin above its isoelectric point were studied by pH measurements, viscosity and fluorescence spectroscopy. It has been found that three critical concentrations of 22-2-22, referred to as Cinter, Cintra and Ca respectively, can be detected by steady state fluorescence measurements. However, only Cintra can be noted effectively by viscosity measurement. The experimental results indicate that the polymer bound micelles act as transient cross-links resulting in the inter-polymer or intra-polymer association, which is depending on both surfactant and gelatin concentrations. When C22-2-22 > Cinter micelles bound to more than one polymer strand act as transient cross-links between gelatin molecules, that is, inter-molecular association. As C22-2-22 is greater than Cintra, more surfactant micelles tend progressively to envelop and "neutralize" the binding sites of polymer chains and break the inter-chain junctions. And relatively rich surfactant micelles made each gelatin strand accommodate surfactant micelle which bind with several sites of the same polymer chain, i.e., the intra-polymer association occurs. Finally one gelatin chain may bind several surfactant micelles. However if Cgelatin reaches the overlap concentration C* the intra-polymer association may be screened by the entanglement of polymer chains.